Analysis of the Effect of Digital Color Grading Techniques on Aesthetic Perception and Emotional Response in a Short Rice Farming Video - Yoga Prisma Yuda; Inung Diah Kurniawati; Muh.Nur Luthfi Azis (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Digital color grading is a post-production technique used to adjust hue, saturation, luminance, and color temperature to enhance visual mood, aesthetic appeal, and emotional expression. In agricultural-themed videos, color adjustments significantly influence how audiences perceive naturalness, warmth, authenticity, and emotional closeness to rural environments. This study aims to examine the influence of three digital color grading techniques—warm tone, cool tone, and neutral tone—on viewers’ aesthetic perception, emotional response, visual comfort, and thematic suitability when watching a two-minute video of rice-field activities. An experimental design was employed, involving 30 respondents who evaluated three graded versions using a 5-point Likert questionnaire. The analysis relied solely on descriptive statistics, including mean, standard deviation, and frequency distribution, to identify perceptual tendencies across tone variations. The findings indicate that warm tone tends to improve aesthetic judgment and emotional positivity, while neutral tone contributes to higher visual comfort due to its natural appearance. Cool tone, although perceived as calm and professional, shows lower emotional engagement in this context. These results align with previous Indonesian multimedia studies emphasizing the role of color tone in shaping viewer interpretation of documentary and thematic video content. This research contributes practical insights for multimedia practitioners, educators, and content creators working with agricultural visual materials. The outcomes may guide color grading decisions for rural documentaries, educational videos, or promotional media by highlighting how tone selection influences viewer perception.